Deradikalisasi Pemuda melalui Pendekatan Pemikiran Islam Kontemporer - Inul Katika Putri; Vyna Mar’atul Muflichah; Dewi Sartika Syam; Kurniati Kurniati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Youth radicalization is a serious issue that threatens social harmony, national stability, and the sustainability of nationhood in Indonesia. Various reports indicate that nearly one-third of terrorism perpetrators over the past decade have come from young people, signaling ideological vulnerability among the productive age group. This article aims to propose a youth deradicalization approach through contemporary Islamic thought, emphasizing rationality, openness of thinking, and humanism as its main foundations. This study employs a qualitative method with a literature review approach by analyzing the works, ideas, and thoughts of contemporary Islamic scholars and examining their relevance in the context of youth development and empowerment. The findings show that contemporary Islamic approaches that emphasize critical reasoning, dialogue, and respect for humanity are effective in shaping moderate attitudes, fostering social awareness, and strengthening an inclusive and tolerant Islamic identity. Therefore, this article recommends that religious education be integrated into curricula that emphasize the values of religious moderation, respect for diversity, and the rejection of violence. This approach is expected to help young people become more tolerant, adaptive, and resilient against the influence of extremist ideologies that are harmful to society.